(untitled) (Asian Education Studies, 2016)
DI flashcards have been proven be improve student performance in a wide range of subject matter-areas. Students with memory issues may well benefit from being taught with DI flashcards. Employing a count-by series has been employed by classroom teachers to teach multiplication. Count-bys can provide students an easy transition from addition to multiplication. This project implemented DI flashcards with a count by series to improve the performance of a single elementary school student having difficulty in math. These two procedures were evaluated in an ABABCB single case design. The results indicated that our participant’s performance increased when these two procedures were combined. Finally generalization was carried out with new math facts. When DI flashcards and the count by series charts were again employed with his new math facts, his performance quickly increased. Suggestions for future research employing DI flashcards and generalization of treatment outcomes were also provided.